URGENSI PENANAMAN NILAI KARAKTER SPIRITUAL KEAGAMAAN dan INTEGRITAS DALAM DUNIA PENDIDIKAN - Imam Hanafi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
Education in Indonesia is the focus of government attention, because of many problems currently affecting the state of Indonesia are in the field of education, the problem is mainly due to the lack of character owned by students or teachers who should be role models for their students. To answer these issues, re-planting of character values is considered a solution of all it. The many values of that must be invested in every individual from an early age, especially for Muslims is the religious spiritual character (ma'rifatullah) and the character of integrity (honesty-trust).